2015
DOI: 10.1108/ijbm-07-2014-0102
|View full text |Cite
|
Sign up to set email alerts
|

Serving the poor: captive market CSR and repurchase intention

Abstract: Purpose – The purpose of this paper is to examine whether corporate social responsibility (CSR) activities of the firm affect poor captive consumers’ repurchase intentions, and whether or not CSR activities may moderate established relationships that drive repurchase intentions. Design/methodology/approach – A survey was administered to 201 poor microfinance borrowers at the bottom of the pyramid in India in a cross-sectional field study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…CSR plays another important role as a marketing communication tool in the process of creating a plausible corporate image that carries a socially responsible depiction of a firm (Jahdi, 2013). CSR as a marketing communication tool positively enhances firm image and reputation (Saeidi et al, 2015;Tingchi Liu et al, 2014;Jose et al, 2015). Through using CSR as a communication tool, companies attempt to understand consumers' needs and wants and familiarize customers with the companies' offerings.…”
Section: Traumatic Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSR plays another important role as a marketing communication tool in the process of creating a plausible corporate image that carries a socially responsible depiction of a firm (Jahdi, 2013). CSR as a marketing communication tool positively enhances firm image and reputation (Saeidi et al, 2015;Tingchi Liu et al, 2014;Jose et al, 2015). Through using CSR as a communication tool, companies attempt to understand consumers' needs and wants and familiarize customers with the companies' offerings.…”
Section: Traumatic Eventsmentioning
confidence: 99%
“…Sullivan-Taylor and Wilson (2009) show that CSR strategies that manage the threat of terrorism in the tourism industry also improve the level of organizational resilience. In a study on whether CSR activities affect consumer repurchase intention, Jose et al (2015) show that risks have a negative impact on bank customers' attitudes and they suggest CSR reduce and limit financial risks. In other words, this argument suggests that marketing activities can change consumer attitudes even though consumers are already exposed to or have experienced traumatic accidents or risks and have a negative attitude toward the company.…”
Section: Traumatic Eventsmentioning
confidence: 99%
“…CSR is one of pro-poor policies for development [3] and one of the public services carried out by the government to the poor [4]. According to World Bank, CSR is the commitment of business to contributes to sustainable economic, working with employees, their families, the regional community and society at large to improve their quality of life in ways that are both good business involved and its stakeholders [5].…”
Section: Resultsmentioning
confidence: 99%
“…When firms deviate from ethical and social obligations in society, customers will have a negative evaluation of those firms (Jose, Khare, & Buchanan, 2018), which may even result in sanctions toward irresponsible companies (Dawkins & Lewis, 2003; Shim & Yang, 2016; Smith, 2000). Yet, studies have found that there is a relationship between CSR performance and customer's support intentions (Abdeen, Rajah, & Gaur, 2016; Jose, Khare, & Buchanan, 2015). It is well documented that consumers' perceptions of CSR have a positive impact on their purchase intentions (Alniacik, Alniacik, & Genc, 2011; Bianchi, Bruno, & Sarabia‐Sanchez, 2019; Jones, Reilly, Cox, & Cole, 2017; Mohr, Webb, & Harris, 2001; Pekkanen, Pätäri, Albadera, & Jantunen, 2018; Sen, Bhattacharya, & Korschun, 2006).…”
Section: Introductionmentioning
confidence: 99%